First one = 9x3=27
Second one 12x9=108
3rd one = 3x4=12
Idk what that last one is
A. The ratio of lynx to mountain lions to wolverines is 2:3:1.
Thus, there are 2 lynx in the ratio. If there were 6 lynx, we would have to multiply all of the numbers in the ratio by 3 (because 6/2 = 3) to keep the ratio in the same proportion.
Therefore, because there is 1 wolverine in the ratio, and 1 * 3 = 3, if there were 6 lynx, there would be 3 wolverines.
b. We can use the same ideas that we had in part a to help us in part b.
There are 3 mountain lions in the ratio, but there are 15 mountain lions in the problem. Thus, the multiplier is 5, because 15/3=5.
Therefore, because there are 2 lynx in the ratio, and 2*5 = 10, if there were 15 mountain lions, there would be 10 lynx.
c. There is one wolverine in the ratio, but there are 10 wolverines in the problem. Thus, the multiplier is 10, because 10/1 = 10
Therefore, because there are 3 mountain lions in the ratio, and 3 * 10 = 30, if there were 10 wolverines in the park, then there would be 30 mountain lions.
d. The total number of lynx, mountain lions, and wolverines is 30.
To find out how many of each animal there should be, we must make an equation using the ratio and the variable x.
2x + 3x + 1x = 30
This equation means that the total number of animals together is 30, which is true. Now let's simplify by combining like terms.
6x = 30
Finally, we can simplify by dividing both sides by the coefficient of x, or 6.
x = 5
Thus, going back to our original equation, we know that the amount of lynx is 2x, mountain lions is 3x, and wolverines is 1x.
Lynx = 2x = 2(5) = 10 lynx
Mountain Lion = 3x = 3(5) = 15 mountain lions
Wolverines = 1x = 1(5) = 5 wolverines
Hope this helps! :)
Answer:
Possible C:
(1 , 1 + 3sqrt(3))
(1 , 1 - 3sqrt(3))
Step-by-step explanation:
AB = 6 units
Midpoint of AB is (1,1)
C would be at x = 1
So, (1,y)
(y-1)² + (1+2)² = 6²
(y-1)² = 36 - 9
(y-1)² = 27
y - 1 = 3sqrt(3)
y - 1 = -3sqrt(3)
y = 1 + 3sqrt(3)
y = 1 - 3sqrt(3)
Answer:
It will take Jade (2x + 5) minutes
Step-by-step explanation:
Let us find the expression that represents the time Jade will take
∵ Binh takes x minutes to ride to his friend’s house
∴ The time Binh takes = x minutes
∵ 5 more means + 5
∵ Twice means × 2
∵ Jade takes 5 minutes more than twice as long as Binh to ride to their
friend’s house
→ Multiply the time Binh takes by 2 and add the product by 5
∵ Binh takes x minutes
∴ The time Jade takes = 2 × x + 5
∴ The time Jade takes = 2x + 5 minutes
∴ It will take Jade (2x + 5) minutes